Performance and bacterial community composition of volcanic scoria particles (VSP) in a biological aerated filter (BAF) for micro‐polluted source water treatment. (23rd May 2019) - Xie, Kang; Wang, Bin; Qiu, Liping; Zhang, Shoubin; Wang, Jiabin; Liu, Guicai; Sun, Shaofang
Abstract: A laboratory‐scale biological aerated filter (BAF), using volcanic scoria particles (VSP), was used for treating micro‐polluted source water. The system reached a steady‐state stage and performed better at removing pollutants. In steady‐state stage, the effluent ammonia ( NH 4 + - N ) and chemical oxygen demand (COD) were consistently maintained below 0.3 and 3 mg/L, respectively. Both the NH 4 + - N and COD removal efficiencies decreased with shorter hydraulic retention time (HRT). The effluent NH 4 + - N and COD exceeded health standards at 15 min of HRT. Although performance was relatively poor for VSP‐BAF at low temperature, the NH 4 + - N removal still achieved the drinking water quality standard. The influences of influent NH 4 + - N and COD concentration changes were similar to that of temperature. A better performance was observed in NH 4 + - N removal under higher influent NH 4 + - N concentrations. In contrast, the effluent COD was more than 3 mg/L when the influent COD concentrations increased to about 9 mg/L. The phylogenetic and cluster analyses indicated that the effect of HRT on bacteria community structure was higher than that of temperature, while the ammonia‐oxidizing bacteria (AOB) are sensitive to temperature. The main phyla identified in total bacteria communities were Proteobacteria, Bacteroidetes, Firmicutes, and Nitrospirae. The main AOB were Nitrosomonadales and an uncultured ammonia‐oxidizing bacterium. Practitioner points: The BAF using VSP obtained a good performance for treating micro‐polluted source water. The influence of HRT on the system was more significant than that of temperature. The system is resistant to NH 4 + - N concentration shocks while is unable to withstand the COD increasing. The effect of HRT on bacteria community structure was significantly higher than that of temperature. Abstract : The micro‐polluted source water treatment using VSP‐BAF.